Preparation of tabular corundum aggregate from different sources alumina raw powder: Sintering kinetics and establishment of kinetics model. Issue 12 (15th June 2022) - Ma, Jiuhong; Zhao, Huizhong; Yu, Jun; Zhang, Han; Shi, Lida; Zhao, Yi; He, Jian; Liu, Hongbo; Li, Bin
Abstract: In this paper, we report the use of four types of commercial alumina raw powders as raw materials for the preparation of tabular corundum aggregates under the same conditions. The influence of the transition phases of alumina raw powder on the sintering kinetics of tabular corundum is discussed, the sintering model of materials with pseudomorphic structure is established, and the mechanisms underlying the different performances of various commercial tabular corundum samples are evaluated. The following conclusions were drawn based on the results of the study. (1) A double tetrakaidecahedron model was established and was shown to satisfactorily describes the sintering mechanism of alumina raw powder with pseudomorphic structure, which accords with the porosity change trend of sintered body and provides a basis for perfecting the sintering theory. (2) Compared with the other transition phases, γ-Al2 O3 shows the largest phase transformation volume contraction, which provides the driving force for the sintering process via an increase in surface energy and mainly acts in the densification and grain growth stages. Thus, high-quality refractory raw materials are prepared with optimized physical properties and Intracrystalline pores or pore clusters in the crystal structure. The preparation of these high-quality refractory products is of importance for prolonging the life of these materials and also meeting rising energy demands.